CASO BRUXA DA SAPOLÂNDIA: representações sociais no jornalismo policial de Campo Grande (MS) - JOÃO HERMINIO PRESTES VIANA (2024)
This research investigates the longevity and persistence of social representations involving the "Sapolândia Witch" case, a police episode that shook Campo Grande (MS) in the late 1960s due to the cruelty of the facts reported in a very peculiar way by Diário da Serra, an important newspaper of the Diários Associados Group that circulated in the city between 1968-1998. Four children were allegedly killed in "black magic" rituals, and their bodies were buried in the backyard of the house where Célia de Souza lived, the woman who would be forever known as the "Witch of Sapolândia." Between shock and outrage, the population followed all the details through the newspaper. Five decades later, the story remains alive in the popular imagination, and the Sapolândia Witch has become an urban legend immune to the passage of time, despite Célia having been acquitted of all charges in court. It was possible to evaluate the power of social representations disseminated by the press and reflect on the care and responsibility of reporters when producing their text. The main theoretical framework used was the Theory of Social Representations, with Content Analysis as the methodological approach.